Construção e avaliação de um ambiente virtual de aprendizagem voltado à Educação em Ciências, Química Verde e Sustentabilidade Socioambiental - Souza, Fábio Fontana de (2013)
The Learning Management System (LMS) has become extremely attractive because of the development of tools that enable synchronous and asynchronous interaction between users connected to the internet. The system has being adopted by many educational institutions, especially in the higher education ones. In this paper we describe the development, use and evaluation of a course built on the LMS Moodle with the main objective of checking its potential to complement the lessons of subject "Experimentação para o ensino de Química 1 e 2", offered to undergraduate students in Chemistry of Universidade Federal de São Carlos (UFSCar). Moodle course area was built to provide students some materials and activities that allow communication about issues related to experiment on teaching with a focus on environmental sustainability and Green Chemistry. Undergraduate chemistry students voluntarily participated in the research during the first and second semesters of 2012. The data was collected through the textual productions in forums with the participation of all undergraduates and where there was a questionnaire and a final evaluation of the course "Experimentação para o ensino de Química 2". Throughout the course the students used the environment as a privileged place to express themselves and to build the collective knowledge, since this tool has provided to licensees recognition and appropriation of another training space that supports debate which is not possible in the classroom very often. We conclude that virtual learning environments focused on teacher education can enhance the work done in the classroom.